Controlling and Monitoring Crack Propagation in Monolayer Graphene Single Crystals. (25th May 2022) - Zhao, Xin; Mao, Boyang; Liu, Mufeng; Cao, Jianyun; Haigh, Sarah J.; Papageorgiou, Dimitrios G.; Li, Zheling; Young, Robert J.
Abstract: The evolution and propagation of cracks in exfoliated monolayer graphene single crystals and their associated stress fields are studied using Raman spectroscopy as a strain sensor. Such stress fields are found to extend over several microns, and their analysis leads to the fracture behavior of graphene being interpreted using linear elastic fracture mechanics. It is shown that propagation of a sharp crack occurs at a critical stress intensity factor K c ≈ 4.0 MPa m 1/2, similar to the earlier findings of theoretical simulations. In contrast, a blunt crack lying along an irrational direction of the crystal is found to have a less localized stress field at the crack tip and propagate at a value of K c > 9 MPa m 1/2 . It is also shown that once crack propagation takes place, the cracks rotate to become aligned approximately perpendicular to the tensile axis, regardless of the crystallographic orientation of the graphene. Based upon this, a simple strain engineering method is proposed to control the propagation of cracks. This has important implications for the use of graphene in practical applications and suggests a simple method to control the formation of cracks in graphene through the application of strain. Abstract : The evolution and propagation of cracks in graphene and the stress field in the vicinity of cracks are monitored experimentally, allowing the critical stress intensity factor K c to be determined as ≈4.0 MPa m 1/2 . A simple strain engineering method is demonstrated to control the crack propagation, regardless of the crystallographic orientation of the graphene, through the application of strain.